Nitrogen recovery by a halophilic ammonium-assimilating microbiome: A new strategy for saline wastewater treatment. (1st December 2021) - Zhang, Mengru; Han, Fei; Li, Yuke; Liu, Zhe; Chen, Hao; Li, Zhe; Li, Qian; Zhou, Weizhi
Highlights: A marine bacterium with the biofilm-forming capability was screened. An ammonium-assimilating microbiome was constructed based on the marine bacterium. Ammonium was removed and recovered into biomass through assimilation. Efficient nutrient removal was achieved by this microbiome in saline wastewater. This halophilic microbiome maintained robustness and functional stability. Abstract: Wastewater with high salinity is one of the major challenges for conventional wastewater treatment. Although nitrogen management is vital for wastewater treatment, efficient strategies for nitrogen recovery and removal from saline wastewater remain challenging. Here we propose microbial ammonium assimilation to achieve efficient nitrogen removal and recovery into biomass from saline wastewater without gaseous nitrogen release opposite to the conventional wastewater treatment, . We find one marine bacterium Psychrobacter aquimaris A4N01 with the ability to form sedimentary granular biofilms that can be engineered to construct an efficient ammonium-assimilating microbiome followed the bottom-up design. We demonstrate that the microbiome removes ammonium through assimilation without reactive nitrogen intermediates and gaseous nitrogen emission, according to the functional gene abundance and nitrogen balance. More than 80% of ammonium, total nitrogen and total phosphorus are removed and recovered into biomass, with more than 98% of COD removed from saline wastewater. As one prototypic microbe to form ammonium-assimilating biofilms, Psychrobacter aquimaris A4N01 plays key role in nutrient metabolism and microbiome construction. We stress that ammonium assimilation with a clear and short pathway is a promising method in future saline wastewater treatment and sustainable nitrogen management. Graphical abstract: Image, graphical abstract